Buddhachinaraj : The Conveying Symbol of Social and Cultural Meaning - สอนวดี พระปลัดเมธี (JOURNAL OF RATTANA PAÑÑĀ, 2020)
Buddhachinaraj had built in the Sukhothai period; it recognized the most beautiful Buddhist image in Thailand, which is the creation of Buddhist sculpture. In addition to the lord Buddhachinaraj image symbolize the prosperity of Buddhism, and it also shows social and political stability, because in those days the influence of the Khmer empire came to the Sukhothai Kingdom. The architecture in that era, it was built to worship the gods. Brahminical-Hindu religion, When the Kingdom of Sukhothai proclaimed independence from the domination of Khmer. The building religion and the architecture of Buddhism began. The creation of the Buddhachinaraj, it had considered a victory announcement, In addition to the important Buddha invaluable. It is defined as a symbol of Thai. A symbol that expresses the tradition of a good culture, based on the doctrine of life. And it is the ideals of social media, to show the history. The social and cultural development and the Buddhachinaraj are also a symbol to shows the persistence of Buddhism in Sukhothai period to this day.